A Novel Bifunctional Wax Ester Synthase Involved in Early Triacylglycerol Accumulation in Unicellular Green Microalga Haematococcus pluvialis Under High Light Stress - Ma, Haiyan; Zheng, Jie; Li, Yanhua; Zhao, Liang; Zou, Song; Hu, Qiang; Han, Danxiang (Frontiers in Bioengineering and Biotechnology, 2022)
Bulk of neutral lipids, including astaxanthin esters and triacylglycerols (TAGs), are accumulated in the green microalga Haematococcus pluvialis under high light (HL) stress. In this study, a novel bifunctional wax ester synthase (WS) gene was cloned from H. pluvialis upon HL stress. The overexpression of HpWS restored the biosynthesis of wax esters and TAG in neutral lipid-deficient yeast mutant Saccharomyces cerevisiae H1246 fed with C18 alcohol and C18:1/C18:3 fatty acids, respectively. Under HL stress, HpWS was substantially upregulated at the transcript level, prior to that of the type I diacylglycerol:acyl-CoA acyltransferase encoding gene (HpDGAT1). HpDGAT1 is the major TAG synthase in H. pluvialis. In addition, the application of xanthohumol(a DGAT1/2 inhibitor) in the H. pluvialis cells did not completely eliminate the TAG biosynthesis under HL stress at 24h. These results indicated that HpWS may contribute to the accumulation of TAG in H. pluvialis at the early stage under HL stress. In addition, the overexpression of HpWS in Chlamydomonas reinhardtii bkt5, which is engineered to produce free astaxanthin, enhanced the production of TAGs and astaxanthin. Our findings broaden the understanding of TAG biosynthesis in microalgae, and provide a new molecular target for genetic manipulation in biotechnological applications.